Geospatial Model for Flood Mitigation along the Coast of the River Niger in Lokoja, Kogi State, Nigeria - Ijaware Victor Ayodele (European Scientific Journal, ESJ, 2023)
Flooding is a recurring natural disaster with the potential to cause widespread devastation to communities and their environments. This study focuses on the spatiotemporal analysis of flood risk and mitigation strategies in Lokoja, Nigeria, a region susceptible to recurrent flooding due to its location at the confluence of the Niger and Benue rivers. The research aims to provide valuable insights into understanding the dynamics of flooding in Lokoja, assessing its potential impact, and proposing mitigation measures. The study employs an interdisciplinary approach, utilizing Geographic Information Systems (GIS), Remote Sensing (RS), surveying, and statistical techniques to collect, analyze, and model data related to flooding. Data sources include Shuttle Radar Topography Mission (SRTM) imageries, satellite data, historical flood records, and climatic information. Findings reveal a nuanced understanding of flood risk, encompassing the spatial distribution of flooding along Niger River and the contributory factors, such as increasing annual rainfall and river overflow. Also, recent findings from the Federal Government’s flood prediction report indicated that heavy rainfall and potential flooding may impact multiple towns in Nigeria, including those along the Niger River. This highlights the continued importance of proactive flood mitigation efforts, not only in Lokoja but also in various regions susceptible to flooding. The study offers predictive models to anticipate future flooding scenarios. In the light of these findings, this study underscores the significance of comprehensive flood risk assessment and mitigation strategies in Lokoja. The research not only aids in understanding the behavior of the Niger River during heavy rainfall but also provides critical information for developing flood management plans, constructing flood barriers, and enhancing the resilience of the community to flooding. Furthermore, it recommends innovative approaches to harness the recurring dam overflow from Cameroon by channeling the water to Sambisa Forest for agricultural purposes, constructing new turbines for excess electricity generation, and utilizing the water for irrigation during the annual dam release. This study serves as a valuable resource for policymakers, urban planners, and researchers seeking to address the challenges posed by the flooding across Nigeria.